Benefit From a Humanitarian Pediatric Congenital Heart Surgery Program Over a 10-Year Period. Issue 3 (May 2023) - Fürniss, Hannah E.; Leutwyler, Mirjam; Zürn, Christoph; Kroll, Johannes; Kari, Fabian A.; Höhn, René; Fleck, Thilo K.P.; Kubicki, Rouven; Reineker, Katja; Beyersdorf, Friedhelm; Stiller, Brigitte
Background: The charity organization Kinderherzen retten e.V. (KHR) enables humanitarian congenital heart surgery for pediatric patients from low- and middle-income countries at the University Heart Center Freiburg, Germany. The aim of this study was to assess periprocedural and mid-term outcomes of these patients for evaluation of KHR sustainability.Methods: Part one of the study comprised retrospective medical chart analyses of the periprocedural course of all KHR-treated children from 2008 to 2017, and part two a prospective evaluation of their mid-term outcome, assessed by questionnaires concerning survival, medical history, mental and physical development, and socioeconomic situation.Results: Of the 100 consecutively presented children from 20 countries (median age 3.25 years), 3 patients were not invasively treatable, 89 underwent cardiovascular surgery, and 8 received a catheter intervention only. There were no periprocedural deaths. Median postoperative duration of mechanical ventilation, intensive care stay, and total hospital stay was 7 (interquartile range [IQR] 4-21) hours, 2 (IQR 1-3) days, and 12 (IQR 10-16) days, respectively. Mid-term postoperative follow-up demonstrated a 5-year survival probability of 94.4%. The majority of patients received continued medical care in their home country (86.2% of patients), were in good mental and physical condition (96.5% and 94.7% of patients, respectively), and able to engage in age-appropriate education/employment (98.3% of patients).Conclusions: Cardiac, neurodevelopmental, and socioeconomic outcomes of patients treated via KHR was satisfactory. Thorough pre-visit evaluation and close contact with local physicians are crucial when providing this high-quality, sustainable, and viable therapeutic option for these patients.